Fragility-based sensitivity analysis on the seismic performance of pile-group-supported bridges in liquefiable ground undergoing scour potentials. (1st November 2019) - Wang, Xiaowei; Ye, Aijun; Ji, Bohai
Highlights: A fragility-based Tornado diagram approach is proposed for sensitivity analyses. Sensitivity rankings of 14 parameters for fragility estimates of bridges are identified. Impacts of scour depths and damage limit states on the sensitivity rankings are revealed. Seismic failure mechanisms of bridges under liquefaction and scour is preliminarily revealed. Outcomes can assist in designs and retrofits of bridges in liquefiable soil undergoing scour. Abstract: Characterizing the effect of varying model parameters on the seismic performance of bridges is a desirable assistance to retrofits of existing bridges and designs of new bridges, especially for those in complex geotechnical conditions where scour and liquefaction potentials are involved. This paper aims to rank the sensitivity of fourteen structural and soil parameters for seismic performance assessment of pile-group-supported bridges in liquefiable ground undergoing scour potentials. To this end, a fragility-based Tornado diagram method for sensitivity analyses is proposed first in this study. An experimentally validated soil-foundation-bridge coupled finite element model considering scour and liquefaction effects is adopted and excited by a set of real ground motions for fragility analyses. Results indicate that the effect of scour depth slightly influence the most sensitive parameters, mainly including column height and diameter and pile diameter, for the performance of bridge components (i.e., bearing, column and pile). However, the increase of scour depth does downgrade the relative sensitivity of column-associated ones (e.g., column height and axial compressive ratio) and soil-related ones (i.e., loose and dense sand relative densities), while upgrade that of the pile-associated ones (e.g., pile diameter, center-to-center distance and longitudinal reinforcement ratio). In addition, to abide the capacity design principle that columns should fail before pile foundations, designs or retrofits of bridges using relatively larger pile diameter, column height, material strengths and longitudinal/transverse reinforcement ratios, together with smaller column diameter and pile center-to-center distance are recommended for mitigating scour and liquefaction effects on the seismic performance of pile foundations.